2018
DOI: 10.1002/jcp.27584
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxytyrosol from olive fruits prevents blue‐light‐induced damage in human keratinocytes and fibroblasts

Abstract: Skin aging is a complex biological process influenced by a combination of endogenous or intrinsic and exogenous or extrinsic factors due to environmental damage. The primary environmental factor that causes human skin aging is the ultraviolet irradiation from the sun. Recently, it was established that the long‐term exposure to light‐emitting‐diode‐generated blue light (LED‐BL) from electronic devices seems to have a relevant implication in the molecular mechanisms of premature photoaging. BL irradiation induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 45 publications
(76 reference statements)
2
53
0
Order By: Relevance
“…Recently, Rascalou et al [ 31 ] demonstrated that the cell cultures exposure to 99 J/cm 2 of blue light is equivalent to cells exposed to the screen of an electronic device for 1952 h in real life. Thus, in our in vitro system, we tried to obtain a model of LED-BL exposition treating NCTC 2544 with 5, 10, 15, 25, 45 50, and 85 J/cm 2 [ 43 ]. The MTT results showed a dose-dependent reduction of viability and confirmed the dose of 45 J/cm 2 inducing cell mortality near to 50% (IC 50 value= 47.8 ± 2 %).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Rascalou et al [ 31 ] demonstrated that the cell cultures exposure to 99 J/cm 2 of blue light is equivalent to cells exposed to the screen of an electronic device for 1952 h in real life. Thus, in our in vitro system, we tried to obtain a model of LED-BL exposition treating NCTC 2544 with 5, 10, 15, 25, 45 50, and 85 J/cm 2 [ 43 ]. The MTT results showed a dose-dependent reduction of viability and confirmed the dose of 45 J/cm 2 inducing cell mortality near to 50% (IC 50 value= 47.8 ± 2 %).…”
Section: Discussionmentioning
confidence: 99%
“…By demonstrating that EVOO phenols exert anti‐inflammatory effects on human keratinocytes, our study not only extends these previous findings to also encompass HTy‐Ac, but it shows that human keratinocytes are direct targets of EVOO phenols, which appears translationally interesting in the context of inflammatory skin disorders, as also encouraged by the mentioned studies investigating the potential use of olive oil‐derived compounds in the field of dermatology …”
Section: Discussionsupporting
confidence: 82%
“…HTy is the best studied EVOO‐derived polyphenol and a good candidate for the development of drugs due to its prophylactic and preventive effects in cells and animal models of cancer, lupus, and ischemia‐reperfusion among others . Even though this is the first study to explore the impact of EVOO polyphenols on inflammation‐associated pathways in primary keratinocytes of human origin, HTy was previously described to exhibit chemoprotective and antiaging effects against ultraviolet B (UVB) and blue‐light‐induced damage in human skin cells . In a mouse model of AD, HTy had beneficial effects, reducing erythema intensity and dermatitis and decreasing T‐helper cell cytokines in serum and skin, albeit only in the presence of hydrocortisone .…”
Section: Discussionmentioning
confidence: 99%
“…Three studies reported the antiangiogenic effect of HT [ 32 , 33 , 34 ], while another three studies reported its proangiogenic effect [ 35 , 36 , 37 ]. Three studies examined the antioxidant effect of HT [ 38 , 39 , 40 ]. One study reported the antiaging effect of HT [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies focused on investigating the antimicrobial effect of HT [ 42 , 43 , 44 ]. Moreover, eight studies also included the anti-inflammatory effect of HT as a supplementary outcome of their studies [ 32 , 33 , 34 , 35 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%